Study of the stability of acetaminophen extrudates for 3D printing prepared by hot melt extrusion when stored at different relative humidites - Pereira, Gabriela G. (2021)
Poster presented at the PSWC2020 Virtual (7th FIP Pharmaceutical Sciences World Congress), 4-6 October 2020